Development of ultrafine-grained and nanostructured bioinert alloys based on titanium, zirconium and niobium and their microstructure, mechanical and biological properties - Sharkeev, Yuriy P. 1950-; Eroshenko, Anna Yu; Legostaeva, Elena V.; Kovalevskaya, Zhanna G.; Belyavskaya, Olga A.; Khimich, Margarita A.; Epple, Matthias; Prymak, Oleg; Sokolova, Viktoriya; Zhu, Qifang; Sun, Zeming; Zhang, Hongju (Metals)
For this paper, studies of the microstructure as well as the mechanical and biological properties of bioinert titanium, zirconium, and niobium alloys in their nanostructured (NS) and ultrafine-grained (UFG) states have been completed. The NS and UFG states were formed by a combined two-step method of severe plastic deformation (SPD), first with multidirectional forging (MDF) or pressing into a symmetrical channel (PSC) at a given temperature regime, and then subsequent multi-pass groove rolling (MPGR) at room temperature, with pre-recrystallization annealing. Annealing increased the plasticity of the alloys in the NS and UFG states without changing the grain size. The UFG structure, with an average size of structural elements of no more than 0.3 mu m, was formed as a result of applying two-step SPD and annealing. This structure presented significant improvement in the mechanical characteristics of the alloys, in comparison with the alloys in the coarse-grained (CG) or small-grained (SG) states. At the same time, although the formation of the UFG structure leads to a significant increase in the yield strength and tensile strength of the alloys, their elastic modulus did not change. In terms of biocompatibility, the cultivation of MG-63 osteosarcoma cells on the polished and sandblasted substrates demonstrated high cell viability after 10 days and good cell adhesion to the surface.